2018
DOI: 10.1093/rpd/ncy135
|View full text |Cite
|
Sign up to set email alerts
|

Application of Reflectance Confocal Microscopy for Early Diagnosis of Radiation-Induced Acute Dermatitis in Radiosensitive Patient: Case Study

Abstract: According to the guidelines on cancer treatment up to 52% of newly diagnosed cancer patients should be treated with external beam radiotherapy. Ionizing radiation (IR)-induced skin injury (radiation dermatitis) occurs in up to 95% of radiotherapy patients and can manifest from mild erythema till necrosis and ulceration. Individual radiosensitivity was proposed to be an important factor for the development of adverse reactions to IR. Therefore, assessment of radiosensitivity could be useful in predicting and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
1
6
0
1
Order By: Relevance
“…8 Additionally, the dermo-epidermal junction more frequently appeared blurred in enrolled patients (P < 0.05), which may be caused by the vascular degeneration of basal cells and the presence of spongiosis. 1,9,10 To the best of our knowledge, this is the first study to describe D-OCT features of the skin of patients undergoing RT, which are in line with other non-invasive imaging devices. These outcomes underline the importance of treating the skin of the target RT area with topical protective therapies, independently of clinical signs to prevent consequences, such as ulcers and cutaneous malignancy.…”
supporting
confidence: 62%
See 2 more Smart Citations
“…8 Additionally, the dermo-epidermal junction more frequently appeared blurred in enrolled patients (P < 0.05), which may be caused by the vascular degeneration of basal cells and the presence of spongiosis. 1,9,10 To the best of our knowledge, this is the first study to describe D-OCT features of the skin of patients undergoing RT, which are in line with other non-invasive imaging devices. These outcomes underline the importance of treating the skin of the target RT area with topical protective therapies, independently of clinical signs to prevent consequences, such as ulcers and cutaneous malignancy.…”
supporting
confidence: 62%
“…Onychomycoses represent up to 50% of all nail diseases. 1 Subjects with immunosuppressive conditions are particularly vulnerable. In a review of 34 articles, the prevalence in patients with DM2 was 8.75%, compared with 3.22% in the general population.…”
Section: Data Availability Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Over 95% of patients that are exposed to ionizing radiation report adverse effects such as erythema, edema and dryness of the skin, itching, dry or moist desquamation, soreness, and, in extreme cases, skin necrosis. [3][4][5] These symptoms are known as radiation dermatitis. 5 This skin inflammation is divided into acute radiation dermatitis, which appears within the first four weeks of treatment and chronic radiation dermatitis, which can be observed even years after radiation.…”
Section: Introductionmentioning
confidence: 99%
“…RCM has been used for the evaluation of ARD skin changes, and it was determined that RCM can detect IR-induced skin changes, but the results were obtained from only six patients [ 27 ]. In one patient case study, it was also demonstrated that IR-induced skin changes in RCM images appear earlier than the occurrence of clinical symptoms [ 28 ].…”
Section: Introductionmentioning
confidence: 99%